Ritme kebiasaan makan ikan Bandeng (Chanos chanos Forskal) selama 24 jam pada tambak ekstensif - Abdul Hafizan Ilmani; Leni Handayani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
This study aims to determine at what time the milkfish (Chanos chanos Forskal) eat in the pond and when the peak of milkfish eating occurs. This research was conducted in the ponds area of Sungai Undang Village, Seruyan Regency, with a descriptive research method. The research was carried out in July 2020. The parameters observed in this study were the presentation of stomach fullness and the sampling time of the milkfish so that it can be determined how the milkfish eating rhythm is for 24 hours. The results showed that milkfish started eating at 06.00 WIB until they finished digesting food at 22.00 WIB, meaning that milkfish took about 18 hours to carry out foraging activities until the digestion process was complete. The peak occurrence of eating milkfish is at 12.00 WIB. Keywords : chanos, milkfish, eating rhythm